Cerebral ventricular changes associated with transitions between normal cognitive function, mild cognitive impairment, and dementia. - Carmichael, Owen T; Kuller, Lewis H; Lopez, Oscar L; Thompson, Paul M; Dutton, Rebecca A; Lu, Allen; Lee, Sharon E; Lee, Jessica Y; Aizenstein, Howard J; Meltzer, Carolyn C; Liu, Yanxi; Toga, Arthur W; et al. (Alzheimer Dis Assoc Disord, 2007)
Expansion of the cerebral ventricles may occur at an accelerated rate in subjects with dementia, but the time course of expansion during transitions between normal cognitive function, mild cognitive impairment (MCI), and dementia is not well understood. Furthermore, the effects of cardiovascular risk factors on rate of ventricular expansion are unclear. We used a fully automated segmentation technique to measure change rate in lateral ventricle-to-brain ratio (VBR) on 145 longitudinal pairs of magnetic resonance images of subjects in the Cardiovascular Health Study Cognition Study from the Pittsburgh Center. A multivariate model analyzed VBR change rate, accounting for dementia statuses at both imaging times (normal, MCI, or dementia), age, sex, education, race, magnetic resonance-defined infarcts, Center for Epidemiology Studies Depression Scale, baseline ventricular volume, and cardiovascular risk factors. VBR change was faster in subjects who were demented or transitioned from MCI to dementia, compared with subjects normal at both images and subjects who transitioned from normal to MCI or dementia. Patients with diabetes had faster VBR change. Ventricular expansion may accelerate late in the progression from normal cognitive function to dementia, and may be modulated by diabetes.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Cerebral Ventricles; Cognition Disorders; Dementia; Disease Progression; Female; Humans; Image Processing, Computer-Assisted; Longitudinal Studies; Magnetic Resonance Imaging; Male; Risk Factors; Severity of Illness Index; Time Factors

Ventricular volume and dementia progression in the Cardiovascular Health Study. - Carmichael, Owen T; Kuller, Lewis H; Lopez, Oscar L; Thompson, Paul M; Dutton, Rebecca A; Lu, Allen; Lee, Sharon E; Lee, Jessica Y; Aizenstein, Howard J; Meltzer, Carolyn Cidis; Liu, Yanxi; Toga, Arthur W; et al. (Neurobiol Aging, 2007)
Elevated cerebral ventricular volume may be associated with dementia risk and progression. A fully-automated technique that agreed highly with radiological readings was used to estimate lateral ventricle volume on MR scans done at baseline in 1997-99 of 377 subjects in the Cardiovascular Health Study (CHS) from the Pittsburgh Center. 327 subjects were normal or diagnosed with mild cognitive impairment (MCI) at baseline and were evaluated 4 years later. Baseline ventricular volume was analyzed in multivariate models with age, gender, education level, presence and incidence of cerebral infarcts, and dementia category (normal, MCI, or dementia) at baseline and follow-up as fixed effects. Ventricular volume at baseline was significantly higher among subjects normal at baseline and demented 4 years later. Age, gender, education level, and dementia progression were significant factors affecting ventricular volume. Ventricular volume was higher in dementia compared to MCI, higher in MCI compared to controls, and higher in Possible-Alzheimer's-disease (AD) dementia compared to Probable-AD. Larger ventricles in healthy subjects may indicate susceptibility to, or progression of, dementia-related pathology.
Keywords: Aged; Aged, 80 and over; Aging; Cognition Disorders; Cross-Sectional Studies; Dementia; Disease Progression; Female; Follow-Up Studies; Humans; Lateral Ventricles; Linear Models; Magnetic Resonance Imaging; Male; Predictive Value of Tests; Prospective Studies; Retrospective Studies; Time Factors